A study of Afghan university graduates’ perspectives on the relevance of higher education (Journal of Applied Learning and Teaching, 2024)
This study delves into the perspectives of graduates on higher education in Afghanistan. Utilizing a stratified sampling approach, 284 graduates from Samangan Higher Education Institute were surveyed. The sample size was determined using the Cochran method with a 5% error rate. Over three weeks in November 2023, responses from 121 graduates of the year 2021 and 163 graduates of the year 2022 were gathered, with males comprising 64.8% and females incorporating 35.2% of the respondents. The findings highlight that individual preferences were the primary influencers in selecting majors, followed by family and friends. Notable disparities in expectation levels emerged between male and female graduates, with only 30% of male graduates confirming that their expectations were met, compared to 60% of female graduates. Furthermore, an analysis of employment status among graduates, segmented by gender and faculty, revealed significant discrepancies. Around 60% of male graduates from agriculture and economics faculties are employed, whereas this figure stands at 11% for female graduates. Experience, foreign language skills, and connections are identified as crucial factors in securing employment. Over 60% of female graduates who are employed, work in the private sector. Moreover, 44% of female graduates from the economics faculty and 22% from the agriculture faculty are engaged in small businesses. We recommend implementing programs specifically designed to empower female graduates with entrepreneurship skills. These programs should provide training, mentorship, and resources to help them establish and sustain small businesses or ventures from homes or within their communities. Additionally, there should be efforts to create a supportive ecosystem that facilitates access to markets, finance, and networking opportunities for women entrepreneurs.